Correlation of Inferior Vena Cava diameter and IVC Collapsibility Index with Central Venous Pressure (CVP) in critically ill surgical patients - Singh, Deepak Raj; Thapa, Anurag Singh; Limbu, Yugal; Pandey, Sampanna; Shrestha, Swechha (Journal of Society of Surgeons of Nepal, 2021)
Introduction: Central Venous Pressure is a valuable parameter in the management of critically ill surgical patients in the ICU. Non-invasive methods to extrapolate the volume status of the patient can aid clinicians in expediting proper treatment. The objective of this study is to find a correlation between Inferior Vena cava (IVC) diameter and collapsibility index (CI) with Central venous pressure (CVP) in critically ill surgical patients. Methods: This cross-sectional study included 60 critically ill patients from September 2020 – 31st February 2021. We recorded the patient's age, sex, heart rate, blood pressure, CVP, volume status, IVC minimum, and maximum diameter. After taking consent and explaining the procedure to the patient, the maximum IVC anteroposterior diameter was noted at the end of inspiration and end of expiration in centimeters. IVC collapsibility index was calculated using the formula ([IVCdmax-IVCdmin]/IVCdmax*100%). Following this, the CVP of the patient was measured. Results: Among the patients evaluated, 32 were females. The mean age of the participants was 44.90 ± 15.76 years. The mean central venous pressure maintained was 11.10 ± 2.11cm H2O with an inferior vena cava collapsibility index of 29.69 ± 8.75. There was a negative correlation between CVP and IVC collapsibility index (%), which was statistically significant (r = -0.701, n = 60, p < 0.01). A strong positive correlation between CVP and maximum IVC diameter (r = 0.712, n = 60, p < 0.01) and minimum IVC diameter (r = 0.796, n = 60, p < 0.01) was found. Conclusion: Inferior Vena Cava diameter and IVC Collapsibility Index can be used as a reliable substitute to central venous pressure to determine the patient's volume status.